Developing Students’ Interest in Artistic Values: Forms and Methods (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the pedagogical forms and methods for developing students’ interest in artistic values within the framework of modern educational systems. It emphasizes the integration of art with general subjects, the role of experiential and choice-based learning, and the importance of reflective and project-based approaches in aesthetic education. The research combines theoretical analysis and practical recommendations for teachers. The results demonstrate that integrating artistic activities with interdisciplinary and experiential approaches significantly enhances students’ motivation, aesthetic awareness, and creative self-expression.